Delayed Neurologic Deficit due to Foraminal Stenosis following Osteoporotic Late Collapse of a Lumbar Spine Vertebral Body. (4th March 2013) - Sasaki, Yu; Aoki, Yasuchika; Nakajima, Arata; Shibata, Yoshifumi; Sonobe, Masato; Takahashi, Kazuhisa; Ohtori, Seiji; Nakagawa, Koichi
Abstract : We report an 85-year-old woman with an L3 vertebral body fracture who presented with back pain, bilateral leg pain, and weakness after four months of conservative treatment. Because of unstable pseudoarthrosis, the L3 vertebral body collapsed in the standing position and the L3 nerve root was compressed. The indicated surgery decompressed the L3-L4 foramen and fused the unstable segment. The back pain and neurologic symptoms improved significantly following surgery. We propose that delayed neurologic deficit following an osteoporotic fracture of the lumbar body may be caused not only by retropulsion of vertebral body fragments with significant canal compromise, but also by foraminal stenosis with the late collapse of the vertebral fracture. This new pathomechanism for delayed neurologic deficit has not been previously described. If a collapse takes place in the caudal part of the vertebral body below the base of the pedicle, spine surgeons should be aware of the possibility of foraminal stenosis.